2015
DOI: 10.1007/s11906-015-0586-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Hypertension and Heart Disease

Abstract: Heart disease is a leading cause of death in the United States, and hypertension is a predominant risk factor. Thus, effective blood pressure control is important to prevent adverse sequelae of hypertension, including heart failure, coronary artery disease, atrial fibrillation, and ischemic stroke. Over half of Americans have uncontrolled blood pressure, which may in part be explained by interpatient variability in drug response secondary to genetic polymorphism. As such, pharmacogenetic testing may be a suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…89,90 Identification of PGx markers for beta blockers, thiazide diuretics and angiotensin-converting enzyme inhibitors for the treatment of hypertension and heart failure has been on the focus of intense research for the past two decades and the reader is referred to recent reviews in this area. 9193 …”
Section: Future Challengesmentioning
confidence: 99%
“…89,90 Identification of PGx markers for beta blockers, thiazide diuretics and angiotensin-converting enzyme inhibitors for the treatment of hypertension and heart failure has been on the focus of intense research for the past two decades and the reader is referred to recent reviews in this area. 9193 …”
Section: Future Challengesmentioning
confidence: 99%
“…In view of the facts that elevated blood pressure has evolved as the leading contributor to global burden of disease [ 1 , 2 ] and unsatisfactory control rates achieved by antihypertensive drug treatment [ 3 , 4 ], there is an urgent need for more effective ways to individualize drug therapies in a patient-specific fashion. While pharmacogenomics approaches may be well suited for personalized treatment of the rare varieties of monogenic hypertension [ 5 , 6 ], studies on pharmacogenomics of essential hypertension have shown much less progress [ 7 , 8 ]. Recent genome-wide association studies on genetic associations of specific antihypertensive drug responses have revealed several potential gene loci of interest [ 9 16 ], but the data so far published have lacked consistently replicated findings, and presently there appears to be no clinically useful genetic markers to guide the choice of a given blood pressure-lowering drug.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used antihypertensive drugs in clinical practice are β-blockers, angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers and diuretics. In this context, several pharmacogenetic studies presented evidences on multiple genetic variants (Table 2) associated with response to antihypertensive drugs (68)(69)(70). In this context, several pharmacogenetic studies presented evidences on multiple genetic variants (Table 2) associated with response to antihypertensive drugs (68)(69)(70).…”
Section: Pharmacogenetics Of Antihypertensive Drugsmentioning
confidence: 98%